A Universal Strategy to Design Superior Water‐Splitting Electrocatalysts Based on Fast In Situ Reconstruction of Amorphous Nanofilm Precursors. Issue 43 (12th September 2018) - Chen, Gao; Hu, Zhiwei; Zhu, Yanping; Gu, Binbin; Zhong, Yijun; Lin, Hong‐Ji; Chen, Chien‐Te; Zhou, Wei; Shao, Zongping
Abstract: The development of efficient bifunctional electrodes with extraordinary mass activity and robust stability is an eternal yet challenging goal for the water‐splitting process. Surface reconstruction during electrocatalysis can form fresh‐composition electrocatalysts with unusual amorphous phases in situ, which are more active but difficult to prepare by conventional methods. Here, a facile strategy based on fast reconstruction of amorphous nanofilm precursors is proposed for exploring precious‐metal‐free catalysts with good electronic conductivity, ultrahigh activity, and robust stability. As a proof of concept, an amorphous SrCo0.85 Fe0.1 P0.05 O3− δ (SCFP) nanofilm precursor with weak chemical bonds deposited onto a conductive nickel foam (NF) substrate (SCFP‐NF) is synthesized by utilizing a high‐energy argon plasma to break the strong chemical bonds in a crystalline SCFP target. The quickly reconstructed SCFP‐NF bifunctional catalysts show ultrahigh mass activity of up to 1000 mA mg −1 at an overpotential of 550 mV and extremely long operational stability of up to 650 h at 10 mA cm −2, significantly overperforming state‐of‐the‐art precious‐metal catalysts. Such a strategy is further demonstrated to be a universal method, which can be applied to accelerate the reconstruction of other material systems to obtain various efficient electrocatalysts. Abstract : A universal strategy based on electrochemically induced fast reconstruction of amorphous nanofilm precursors is proposed for exploring ultrahigh mass activity and extremely stable bifunctional water‐splitting catalysts. The facile reconstruction strategy is promising for the development of novel efficient catalysts for other advanced energy conversion and storage devices.